2009
DOI: 10.1007/s00253-008-1740-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of a two-stage growth of DHA-producing marine algae Schizochytrium limacinum SR21 with shifting dissolved oxygen level

Abstract: The culture protocol of Schizochytrium limacinum SR 21, a known docosahexaenoic acid (DHA) producing marine algae was modified in this study to better fit fermentation parameters, particularly control of dissolved oxygen (DO) to the known reproductive and growth biology of the microorganism. The cultures controlled at 50% DO saturation produced a cell density of 181 million cells/ml, whereas cultures with 10% DO produced only 98.4 million cells/ml. A fixed-agitation rate of 150 rpm resulted in an even lower de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 23 publications
1
76
0
1
Order By: Relevance
“…Many species have also been reported to grow heterotrophically on ethanol (Ogbonna et al 1998;Yokochi et al 1998), lactose, galactose and mannose (Liang et al 2009), and molasses (Andrade and Costa 2007). Schizochytrium limacinum produced palmitic acid (16:0) as 45-60 % of their dry weight when supplied with glucose, fructose, or glycerol (Yokochi et al 1998;Chi et al 2009). The effectiveness of these carbon sources varies with the species as well as on the culture conditions such as the light intensity, the pH, dissolved oxygen concentration, and on the presence of other carbon sources.…”
Section: Organic Carbon Sources For Heterotrophic and Mixotrophic Culmentioning
confidence: 97%
See 1 more Smart Citation
“…Many species have also been reported to grow heterotrophically on ethanol (Ogbonna et al 1998;Yokochi et al 1998), lactose, galactose and mannose (Liang et al 2009), and molasses (Andrade and Costa 2007). Schizochytrium limacinum produced palmitic acid (16:0) as 45-60 % of their dry weight when supplied with glucose, fructose, or glycerol (Yokochi et al 1998;Chi et al 2009). The effectiveness of these carbon sources varies with the species as well as on the culture conditions such as the light intensity, the pH, dissolved oxygen concentration, and on the presence of other carbon sources.…”
Section: Organic Carbon Sources For Heterotrophic and Mixotrophic Culmentioning
confidence: 97%
“…Concentrations of glycerol used ranged from 3 to 12 % (Yokochi et al 1998), while Liang et al (2009) reported that 1 or 2 % glycerol resulted in a higher lipid content of microalgae compared to the value obtained with 5 % glycerol. The tolerable concentration of glycerol is within the range of 0.7-10 % (Chi et al 2009). The optimum cassava starch hydrolysate concentration for cell growth and lipid accumulation was 5 g/L, but the values were not significantly different from those obtained with 10 g/L.…”
Section: Organic Carbon Sources For Heterotrophic and Mixotrophic Culmentioning
confidence: 97%
“…Moreover, there are emerging concerns with sustainability of marine resources and with the levels of environmental contaminants (PCBs, dioxins and mercury) in fish. Thus, major efforts have been made to identify or create alternative sources as the current sole main source of DHA may not provide a steady supply for the increasing market demands (Chi et al, 2009;Hauvermale et al, 2006). Since fish obtain n-3 fatty acids from zooplankton which consumes algae, studies now are being diverted to production of DHA directly from its primary source, microalgae (Vazhappilly and Chen, 1998).…”
Section: Ajasmentioning
confidence: 99%
“…Li et al 2008;Chi et al 2009). Control of nitrogen source availability is a well-documented form of manipulation (Flynn et al 1992;Navarro-Angulo & Robledo 1999).…”
Section: Optimization Of Microalgal Growth and Production Of Specificmentioning
confidence: 99%